Karakteristik Fisik Lahan pada Kawasan Lindung DAS Cisangkuy: Land Physical Characteristics in Protected Area of Cisangkuy Watershed - Kusumawardani, Mawar; Sulastri, Neng Wati Ana (Universitas Hasanuddin, 2023)
Cisangkuy Watershed has a function as the water catchment area and the buffer area for environmental safety of Bandung Raya. It carrying capacity status is a restored watershed. One attempt to restore carrying capacity is with the forest and land rehabilitation program. Forming a precise forest and land rehabilitation progam should be supported by data. This study aimed to analyze land physical characteristics in protected area of Cisangkuy Watershed. The method used was overlay technique and descriptive anaysis from spatial data; watersed boundary, topography, soil type, protected area, and critical land; and tabular data of soil characteristics. Texture characteristic of the soils in this area is dominated by clay texture. Soil type with the largest area are Typic Hapludolls - Andic Hapludolls - Oxic Dystropept (2.692,76 ha; 35,16 %) and Oxic Humitropepts - Typic Eutropepts (2.138,43 ha; 27,92 %). Hydrological Soil Group (HSG) classification of the soils varies into A class and B class. The topography characteristics of the area are Rather Steep (16-25 %) and Very Steep (>40%). Area with a slope > 40 % is about 92,96 % of the total protected area.